Effectiveness of long‐term routine pulmonary function surveillance following pediatric hematopoietic stem cell transplantation. Issue 11 (4th November 2013) - Prais, Dario; Sinik, Moran Marx; Stein, Jerry; Mei‐Zahav, Meir; Mussaffi, Huda; Steuer, Guy; Hananya, Shai; Krauss, Aviva; Yaniv, Isaac; Blau, Hannah
Summary Introduction Pulmonary complications following hematopoietic stem cell transplantation (HSCT) are common and often subclinical. Thus, periodic pulmonary function testing (PFT) is mandatory. This study sought to evaluate the effectiveness of long‐term PFT surveillance for children undergoing HSCT and identify potential risk factors. Methods We reviewed long‐term PFT for HSCT patients at a tertiary pediatric center. Inclusion criteria were PFT prior to and at least once following HSCT. Results Fifty‐seven patients performed 202 spirometry and 193 plethysmographic maneuvers; 41 were tested during the first year after HSCT, but only 29 were evaluated consistently long term (2–12 years). FVC and FEV1 decreased gradually suggesting a restrictive ventilatory defect: FVC % predicted [mean ± SD] dropped from 91 ± 14% to 85 ± 17% after 0–24 months and 80 ± 19% beyond 2 years (P = 0.01) whereas FEV1 dropped from 95 ± 16% to 88 ± 19% and 82 ± 20%, respectively (P = 0.002). A slight reduction in TLC was observed. Those undergoing allogeneic HSCT had a greater decline in FVC (P = 0.025) and FEV1 (P = 0.025) as did those conditioned with radiation, regarding both FVC (P = 0.003) and FEV1 (P = 0.002). Decline occurred earlier (≤2 years) after chemotherapy compared with radiation. Seven children had severe irreversible obstruction at >2 years despite therapeutic intervention. Conclusions Most survivors of childhood HSCT maintain almost normal pulmonary function although mild restrictive lung disease may develop, particularly following allogeneic HSCT and conditioning with radiation. Severe airways obstruction developed in a small minority. The surveillance protocol for PFT needs to be followed more stringently to enable intervention possibly before early subclinical changes progress and become irreversible. Pediatr Pulmonol. 2014; 49:1124–1132. © 2013 Wiley Periodicals, Inc.